Electron-optical system of 200 kV gun for the VEPP-5 preinjector - Akimov, V.E.; Kazarezov, I.V.; Kuznetsov, G.I.; Tiunov, M.A. (Вопросы атомной науки и техники, 2004)
The electron gun with a new electron-optical system to match project parameters of the VEPP-5 preinjector is
described. The gun produces the current with 10 A amplitude, pulse duration 2...3 ns at half-height and electron energy 200 keV. The gun has a dispenser cathode 20 mm in diameter and 100 mm spherical radius. The current control is performed by means of molybdenum equipotential grid with the cell size 0.4·0.4 mm and optical transparency
of about 0.68. The experimental results obtained are in good agreement with project parameters. Описано електронну гармату з новою електронно-оптичною системою, що відповідає проектним
параметрам передінжектора VEPP-5. Гармата дає струм 10 А с тривалістю імпульсу 2...3 нс на напіввисоті і
з енергією електронів 200 кеВ. Гармата має диспергуємий катод діаметром 20 мм і радіусом сфери 100 мм.
Керування здійснюється за допомогою молібденової еквіпотенційної сітки з коміркою розміром 0.4·0.4 мм і
оптичною прозорістю близько 0.68. Експериментально отримані результати знаходяться у відповідності з
проектними параметрами. Описана электронная пушка с новой электронно-оптической системой, соответствующая проектным параметрам предынжектора VEPP-5. Пушка дает ток 10 А с длительностью импульса 2…3 нс на полувысоте и
с энергией электронов 200 кэВ. Пушка имеет диспергируемый катод диаметром 20 мм и сферическим радиусом сферы 100 мм. Управление осуществляется посредством молибденовой эквипотенциальной сетки с
ячейкой размером 0.4·0.4 мм и оптической прозрачности около 0.68. Экспериментальные полученные результаты находятся в хорошем соответствии с проектными параметрами.